A Review on Structure - Activity Relationship of Antimicrobial Peptide Magainin 2 - Hasan, Moynul; Islam, Md Monirul; Rahman, Md Mostafizur (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The rapid development of antibacterial resistance has increased the need for the discovery of novel antimicrobial agents. In this context, an emerging class of molecules called antimicrobial peptides (AMPs) has been considered an excellent material for introducing novel antibiotics. Among the wide variety of AMPs, magainin 2 is a 23 residue (GIGKFLHSAKKFGKAFVGEIMNS) peptide obtained from the African clawed frog Xenopus laevis. Different mutants of magainin 2 have been studied to investigate the structure-function relationship. In the present study, we recapitulate the effects of modifying several structural parameters of magainin 2 such as peptide length, amino acid composition, net charge, alpha helicity, hydrophobicity, hydrophobic moment and amphiphilicity on its antibacterial activity. Moreover, we summarized the hemolytic activity regarding these modifications. An optimum change of these parameters would provide desired antibacterial activity with minimum hemolysis. This structurefunction relationship study could be used as a template in designing novel functional antibacterial agents. Dhaka Univ. J. Pharm. Sci. 20(3): 427-434, 2022 (June) Centennial Special Issue